Characteristics of High and Low Crime Neighborhoods in Atlanta, 1980 - Greenberg, Stephanie ([Verlag nicht ermittelbar], 1984)
This study examines the question of how some urban neighborhoods maintain a low crime rate despite their proximity and similarity to relatively high crime areas. The purpose of the study is to investigate differences in various dimensions of the concept of territoriality (spatial identity, local ties, social cohesion, informal social control) and physical characteristics (land use, housing, street type, boundary characteristics) in three pairs of neighborhoods in Atlanta, Georgia. The study neighborhoods were selected by locating pairs of adjacent neighborhoods with distinctly different crime levels. The criteria for selection, other than the difference in crime rates and physical adjacency, were comparable racial composition and comparable economic status. This data collection is divided into two files. Part 1, Atlanta Plan File, contains information on every parcel of land within the six neighborhoods in the study. The variables include ownership, type of land use, physical characteristics, characteristics of structures, and assessed value of each parcel of land within the six neighborhoods. This file was used in the data analysis to measure a number of physical characteristics of parcels and blocks in the study neighborhoods, and as the sampling frame for the household survey. The original data were collected by the City of Atlanta Planning Bureau. Part 2, Atlanta Survey File, contains the results of a household survey administered to a stratified random sample of households within each of the study neighborhoods. Variables cover respondents' attitudes and behavior related to the neighborhood, fear of crime, avoidance and protective measures, and victimization experiences. Crime rates, land use, and housing characteristics of the block in which the respondent resided were coded onto each case record.